Fatty acid profiles and biological activity of Nannochloropsis oculata and Isochrysis galbana, clone t-ISO. Issue 1 (1st September 2022) - Putra, Y; Mustikasari, I; Pangestuti, R; Rahmadi, P; Siahaan, E A
Abstract: The microalgae Nannochloropsis oculata and Tahiti clone Isochrysis galbana (t-ISO) were collected from the Mariculture laboratory, Research Centre for Oceanography, BRIN. Both samples were cultivated and harvested by using a centrifuge. The microalgae biomass obtained was analyzed to determine the fatty acids content. The samples were then extracted, followed by an evaporation process using a rotary evaporator. The microalgae extracts were then tested for its antioxidant activity and antibacterial activity. The results showed that the total fatty acid content of N. oculata (89.82%) was slightly higher than t-ISO (84.97%). The antioxidant activity test showed that t-ISO had slightly higher antioxidant activity than N. oculata (2.4 and 3.33 mg/mL, respectively). As for the results of the antibacterial activity test against the four test bacteria, N. oculata had a slightly lower inhibitory power than t-ISO